2020
DOI: 10.1021/acs.iecr.9b06558
|View full text |Cite
|
Sign up to set email alerts
|

MnOx-Promoted, Coking-Resistant Nickel-Based Catalysts for Microwave-Initiated CO2 Utilization

Abstract: The most important factors in improving the stability of nickel-based catalysts for methane reforming with carbon dioxide (so-called methane dry reforming, MDR) lie both in suppressing carbon formation and inhibiting metal sintering at the high operating temperatures of this process (typically above 700 °C). Many efforts had been made to overcome these challenges, for example, by enhancing metal catalyst-support interactions. In this work, we used microwaves as an energy source to drive the MDR reactions under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 59 publications
(112 reference statements)
0
15
0
Order By: Relevance
“…Figure shows the Ni 2p 3/2 XPS patterns of Ni/AC and bimetallic Cu-Ni/AC. As shown in Figure , Ni 2p 3/2 XPS spectra can be fitted into three components; the peaks around 853.1, 854.6, and 856.6 eV are attributed to Ni metal, Ni oxide (NiO), and Ni hydroxides (Ni­(OH) 2 and NiOOH), respectively. , Additionally, the peak at 861.7 eV is ascribed to the shake-up satellite, which is due to the multielectron excitation of high-valence nickel. , Noticeably, it can be observed from Figure b,c that the peak intensity of Ni metal increases with the introduction of a small amount of Cu (0.5 and 1 wt %), indicating that Cu can effectively promote NiO reduction and facilitate metal Ni exposure. ,, However, as can be seen in Figure d–g, the intensity of Ni 0+ decreases with the introduction of excessive Cu, and the reason may be that excessive Cu can promote the formation of larger metal oxide nanoparticles and NiO–CuO eutectic so as to inhibit NiO reduction . These results are in agreement with the H 2 -TPR results in Figure .…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Figure shows the Ni 2p 3/2 XPS patterns of Ni/AC and bimetallic Cu-Ni/AC. As shown in Figure , Ni 2p 3/2 XPS spectra can be fitted into three components; the peaks around 853.1, 854.6, and 856.6 eV are attributed to Ni metal, Ni oxide (NiO), and Ni hydroxides (Ni­(OH) 2 and NiOOH), respectively. , Additionally, the peak at 861.7 eV is ascribed to the shake-up satellite, which is due to the multielectron excitation of high-valence nickel. , Noticeably, it can be observed from Figure b,c that the peak intensity of Ni metal increases with the introduction of a small amount of Cu (0.5 and 1 wt %), indicating that Cu can effectively promote NiO reduction and facilitate metal Ni exposure. ,, However, as can be seen in Figure d–g, the intensity of Ni 0+ decreases with the introduction of excessive Cu, and the reason may be that excessive Cu can promote the formation of larger metal oxide nanoparticles and NiO–CuO eutectic so as to inhibit NiO reduction . These results are in agreement with the H 2 -TPR results in Figure .…”
Section: Resultsmentioning
confidence: 89%
“…XPS. 43,44 Additionally, the peak at 861.7 eV is ascribed to the shake-up satellite, which is due to the multielectron excitation of high-valence nickel. 19,20 Noticeably, it can be observed from Figure 6b,c that the peak intensity of Ni metal increases with the introduction of a small amount of Cu (0.5 and 1 wt %), indicating that Cu can effectively promote NiO reduction and facilitate metal Ni exposure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…3.1 Catalytic activity for CO 2 reforming of methane at medium temperature The effect of Al and/or Mn promoters was investigated in previous work [25,28,32,33]. It was shown that the catalytic performance of Al-promoted catalysts was higher than that of non-promoted catalyst.…”
Section: The Results and Discussionmentioning
confidence: 99%
“…). 47 The CO 2 utilization route based on CO 2 conversion to solid carbonates involves a complex set of reactions by which CO 2 reacts with Ca, Mg, and/or Fe oxide-bearing phases to yield the corresponding solid carbonate phase. Both gas−solid and aqueous conversion processes have been extensively studied to perform the carbonation reaction.…”
Section: ■ Co 2 Utilization and The Chemical Industrymentioning
confidence: 99%